Pendampingan Masyarakat Dalam Pemahaman Alur Administrasi BPJS Di Fasilitas Kesehatan - Nana Erika; Halimah Tusakdiyah Harahap; Suci Ardiah (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
The community assistance program in understanding BPJS administrative procedures at healthcare facilities aims to improve health literacy and service accessibility for participants of the National Health Insurance (JKN). Many citizens, particularly in rural areas, still face challenges in understanding BPJS registration, referral, and service claim procedures. This activity was carried out through a community-based participatory approach using socialization, service flow simulations, and direct mentoring at healthcare facilities. The results show a significant increase in public understanding of BPJS administrative stages, improved ability to access services independently, and higher satisfaction with healthcare services. The program also strengthened collaboration between communities, health cadres, and BPJS officers in facilitating administrative processes. Therefore, this initiative contributes to improving service efficiency and promoting equitable access to healthcare for all community groups.